Even when historical texts are not an option: extending Karénina Kollmar-Paulenz's approach to a global history of religion - Wettstein, Marion; Wisler, Michaela (AЯGOS, 2024)
Seeking to extend Karénina Kollmar-Paulenz's (2024) methodology for overcoming Eurocentric perspectives in the global history of religion, this commentary evaluates the challenges and alternatives for historiography when textual sources for religious practices are absent. Drawing on research into artistic, visual, and oral practices in Mongolia and the Himalayan region, the authors propose a critical reassessment of the foundational notions of globality, history, and religion.
Sonderheft: Towards a Global History of Religion